Impact and Satisfaction Level Among Members of Women Cooperative - Gerald Talahiban Malabarbas (AIBPM Publisher, 2022)
A cooperative is a business organization structured by volunteers from the community's marginal group with a mutually shared economic and social advantage goal. The study's objective was to determine the impact and satisfaction level of women’s fishpond cooperative among its members. It involved randomly chosen 36 cooperative members from Rosario, Northern Samar, Philippines. An adopted and modified questionnaire was utilized as a data-gathering tool for the respondents' socio-demographic profile, impact, and satisfaction level. The researchers employed a descriptive research design in the conduct of the study. Both descriptive and inferential statistics were used to treat the data with the aid of statistical software. Results revealed that members have agreed that the fishpond cooperative has a socio-economic impact on them. However, they had a neutral opinion regarding their satisfaction level with their membership in the cooperative. A significant difference in the monthly income was found in the respondents’ profile, impact, and satisfaction level to their cooperative membership. Similarly, the monthly income showed a significant relationship to the impact and satisfaction level of their membership in the cooperative. Thus, the study's findings conclude that women’s fishpond cooperative had considerably contributed to their socio-economic condition. However, the members have encountered constraints and challenges in their cooperative activities such as mismanagement, lack of capital and logistics support, and technical know-how on aquaculture production. The researchers recommend that continuous capacity building to all cooperative members is necessary for the sustainability of the women's fishpond cooperative.